Antioxidant Activity Test Of Water, Ethyl Acetat, And N-Heksan Fraction Of Ethanolic Extract Of Sarang Semut (Myrmecodia Pendens Merr. & Perry) - Agus Suprijono; Ariani Hesti Wulan; Arini Dyah Pratiwi (SEKOLAH TINGGI ILMU KESEHATAN NASIONAL, 2022)
Sarang Semut (Myrmecodia pendens Merr. & Perry) is a medical plant contains of flavonoids, tannins, phenolic compounds, polyphenols, and vitamin E. Those substances are potent antioxidants. This research refers to previous research that the ethanol extract of Sarang Semut (Myrmecodia pendens Merr. & Perry) provided antioxidant activity with a mean EC50 of 3.8021 µg/ml. The purpose of this research was to determine the antioxidant activity of the fractions of ethanolic extract of Sarang Semut (Myrmecodia pendens Merr. & Perry) and to determine the highest antioxidant activity of them expressed by EC50. Sarang Semut (Myrmecodia pendens Merr. & Perry) was extracted by soxhletation method using 96% ethanol solvent, then the ethanolic extract partitioned by liquid-liquid fractionation with water, ethyl acetate, and n-hexane. Each fraction at a concentration of 0.9 µg/ml, 1.0 µg/ml, 2.0 µg/ml, 3.0 µg/ml, 4.0 µg/ml, and 5.0 µg/ml were tested by the DPPH method (1,1-diphenyl-2-picrylhidrazyl ) using a spectrophotometer at λ 515 nm and operating time 35 minutes. The result shows the fraction of ethyl acetate has the highest antioxidant activity with a mean EC50 of 2.8821 µg/ml. While the average EC50 fraction of water is 3.8830 µg/ml and n-hexane is 259.9872 µg/ml. From the statistical t test is known that the fraction of water and ethyl acetate have significantly different rates of EC50, while the average of n-hexane fractions were not analyzed statistically because the percentage antioxidant activity of its fraction is not stable.